Characterization of hexokinase gene family members in Glycine max and functional analysis of GmHXK2 under salt stress - Chen, Shuai; Tian, Zengyuan; Guo, Yuqi (Frontiers in Genetics, 2023)
Hexokinase (HXK) is a bifunctional enzyme involved in carbohydrate metabolism and sugar signal sensing. HXK gene family has been extensively discussed in many species, while the detailed investigations of the family in Glycine max have yet to be reported. In this study, 17 GmHXK genes (GmHXKs) were identified in the G.max genome and the features of their encoded proteins, conserved domains, gene structures, and cis-acting elements were systematically characterized. The GmHXK2 gene isolated from G.max was firstly constructed into plant expression vector pMDC83 and then transformed with Agrobacterium tumefaciens into Arabidopsis thaliana. The expression of integrated protein was analyzed by Western Blotting. Subcellular localization analysis showed that the GmHXK2 was located on both vacuolar and cell membrane. Under salt stress, seedlings growth was significantly improved in Arabidopsis overexpressing GmHXK2 gene. Furthermore, physiological indicators and expression of salt stress responsive genes involved in K+ and Na+ homeostasis were significantly lower in GmHXK2-silenced soybean seedlings obtained by virus-induced gene silencing (VIGS) technique under salt stress compared with the control plants. Our study showed that GmHXK2 gene played an important role in resisting salt stress, which suggested potential value for the genetic improvement of abiotic resistant crops.